A global financial transaction tax theory, practice and potential revenues - Atanas Pekanov; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2019)
This study presents in detail the concept of a financial transaction tax (FTT) and the theoretical and empirical evidence in favour and against introducing it, the potential revenues, different implementation designs and its ability to correct various market failures. We analyse the benefits and challenges of introducing a tax on financial transactions, putting special focus on the introduction of such a tax on a world-wide scale. For a number of reasons, international cooperation is deemed a central prerequisite for an efficient FTT. The purpose of the tax is to raise substantial revenues and help dampen excessive financial market speculation and market volatility. An FTT would ensure that the financial sector contributes more substantially to government revenues. In its optimal form, the tax would be broad-based and there will be no financial instrument types exempted. In a second step, we analyse from a political economy perspective the prospects, the current status, and the lessons learnt from the European discussion on the implementation of an FTT. Finally, we calculate the revenue potential of a global FTT and report how much revenues would accrue to specific countries. We estimate that the tax, if imposed globally and taking into account still evasion, relocation and lock-in effects, can bring significant revenues - between 237.9 and 418.8 billion annually. The baseline case delivers 326.9 billion overall for the global economy, which corresponds to 0.43 percent of global GDP. These are lower bounds for potential revenues due to missing data on a number of financial instrument types. For specific countries, in the baseline case this would result in 72.57 billion annual potential revenues for the USA (0.37 percent of GDP), 119.46 billion for the European Union (0.69 percent of GDP), 10.00 billion for Germany (0.27 percent of GDP), 9.99 billion for France (0.39 percent of GDP) and 19.99 billion for Japan (0.41 percent of GDP).
Keywords: 330